Bridging Divides: Christian Education, Non-Foundationalistic, and the Future of Identity in Indonesia - Munte, Alfonso (Jurnal Dialog, 2025)
This paper seeks to identify potential shifts in identity politics, which appear to be evolving in unpredictable ways. This paper observed that, regardless of the underlying dynamics and political shifts, the logical consequences of political turmoil on education, particularly Christian Religious Education, have resulted in the creation of an alienated space at a certain level. Adequate access and care for children with diverse needs, the restructuring of the curriculum, and the 2024 political promise for the education sector are among the key challenges. In light of these observations, this paper examine each phenomenon individually in the role of Gianni Vattimo. This paper employs qualitative research methods, specifically interview techniques, with female subjects, with the aim of elucidating the phenomenon of identity segregation in the context of the livelihood space. The findings demonstrate that Gianni Vattimo's philosophical approach, known as 'weak thought' or 'pensiero debole', is not solely associated with religious hermeneutics. Instead, it also evinces a distinctive interpretation of identity politics, whereby the advancement of specific individual or collective interests exerts a considerable influence on the domain of Christian religious education. Consequently, the value of weak thinking is contingent upon the establishment of mutual respect and love across identities.